APPLICATION OF CRIMINAL SANCTIONS IN LAW NUMBER 41 OF 2014 CONCERNING ANIMAL HUSBANDRY AND HEALTH (STUDY AT THE DELI SERDANG REGENCY AGRICULTURE OFFICE) - Tukijo Tukijo; Isnaini Isnaini; Andi Hakim Lubis (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to analyze the application of criminal sanctions in Law Number 41 of 2014, which plays a crucial role in supporting national food security in the livestock and animal health sector. This law stipulates strict criminal sanctions for violations such as animal abuse, the slaughter of productive fe males, and the distribution of illegal animal products. However, its implementation in Deli Serdang Regency still faces obstacles, such as weak law enforcement, limited resources, and low public awareness. Based on these issues, the research questions are formulated as follows: First, are the criminal sanctions stipulated in Law Number 41 of 2014 effective in preventing violations in the animal health sector? Second, how are the criminal sanctions in Law Number 41 of 2014 concerning Livestock and Animal Health applied to violations in the livestock sector? And Third, what are the obstacles faced in the implementation of criminal sanctions in Law Number 41 of 2014, both in terms of law enforcement and socio-economic aspects of society? The method used in this study is empirical juridical with observation data collection, interviews and document studies, while data analysis uses descriptive analysis. This study found that although normatively Law No. 41/2014 regulates strict criminal sanctions (for example, Articles 86 and 87), its effectiveness in preventing violations in the field of animal health is not optimal. The application of criminal sanctions for violations in the livestock sector (for example, cultivation without a permit, use of non-standard feed, illegal slaughter) is also not consistent, often hampered by the complexity of technical and scientific evidence, as well as the tendency for case resolution to end in coaching or administrative sanctions. The main obstacles faced include the difficulty of proving technical criminal elements, limited human resource capacity (HR) of law enforcement officers in understanding aspects of livestock and animal health, lack of coordination between institutions, and limited facilities and infrastructure (for example, testing laboratories). From a socio-economic perspective, obstacles arise from low legal understanding and awareness among livestock businesses, particularly small-scale ones, as well as economic pressures that encourage them to ignore standards for the sake of profit.